Análisis comparativo del impacto del embarazo adolescente en las trayectorias de vida de las mujeres jóvenes rurales del distrito de Umari, Pachitea, Huánuco - Herrera, Damaris (Pontificia Universidad Católica del Perú, 2019)
The objective of this essay is to analyze the impact of adolescent pregnancy on the family, educational and work trajectories of young women in the rural district of Umari, Pachitea, Huánuco, through a comparative analysis between young women who experienced and not an early motherhood. Based on this, we aim to verify if an adolescent pregnancy event changes the life trajectories of rural adolescents. A qualitative approach is proposed, using semi-structured interviews that were carried out with two groups of young women between 19 and 29 years old. The results point out that family trajectories differ between the two groups, since young mothers tend to live with their partners, dedicating themselves mainly to housework while the young non-mothers continue to live with their families. The educational trajectory is the crucial difference between both groups, since young non-mothers tend to access higher education, in contrast to adolescent mothers, since none of them do. Regarding the work trajectories, it is found that, after a few years, the young mothers begin to work like their non-mother peers, but they access informal, temporary and low-income jobs, while their peers access formal, safe and low-income jobs, and better income, associated with their educational level. However, they share similar trajectories with those young non-mothers who did not study, confirming the hypothesis that adolescent pregnancy, in a context of social vulnerability, does not imply a major change in the life trajectories of the young women, such as the possibilities of social mobility.

El objetivo de este ensayo es analizar el impacto del embarazo adolescente en las trayectorias familiares, educativas y laborales de las jóvenes en el distrito rural de Umari, Pachitea, Huánuco, a través de un análisis comparativo entre las jóvenes que experimentaron y no una maternidad temprana. A partir de esto, se quiere constatar si un evento de embarazo adolescente cambia las trayectorias de vida de las adolescentes rurales. Se plantea un enfoque cualitativo, empleando entrevistas semiestructuradas que se realizaron a dos grupos de mujeres jóvenes entre 19 y 29 años. Resultados: Las trayectorias familiares difieren entre ambos grupos, pues las jóvenes madres suelen vivir con sus parejas, dedicándose principalmente a las labores del hogar. Mientras las jóvenes no madres continúan viviendo con sus familias. La trayectoria educativa es la diferencia crucial entre ambos grupos, pues las jóvenes no-madres suelen acceder a educación superior, en contraste con las madres adolescentes, pues ninguna accede. Sobre las trayectorias laborales, se encuentra que después de algunos años las jóvenes madres empiezan a trabajar al igual que sus pares no-madres, pero acceden a empleos informales, temporales y de bajos ingresos, mientras sus pares acceden a empleos formales, seguros y de mejores ingresos, asociados a su nivel educativo. Sin embargo, comparten similares trayectorias con aquellas jóvenes no-madres que no estudiaron, constatando la hipótesis de que el embarazo adolescente en un contexto de vulnerabilidad social no implica mayor cambio en las trayectorias de vida de las jóvenes, como las posibilidades de movilidad social.
Comparative analysis of the impact of adolescent pregnancy on the life trajectories of young rural women in the district of Umari, Pachitea, Huánuco
Keywords: Licencia por maternidad; Licencia por paternidad; Políticas públicas; Enfoque de género; Family impact analysis; Parental leave; https://purl.org/pe-repo/ocde/ford#5.04.01